2021
DOI: 10.1155/2021/5570885
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Attenuates Lipopolysaccharide-Induced Inflammatory Responses in Macrophage

Abstract: Several studies have reported the efficacy and safety of polyphenols in human health; however, the verification of their efficacy remains insufficient. The aim of this study was to examine whether fisetin, one of flavonoids prevalently present in fruits and vegetables, could suppress lipopolysaccharide- (LPS-) induced inflammatory responses in macrophages. LPS increased proinflammatory mRNA abundance (MCP 1, IL-1β, and iNOS) but were suppressed by fisetin. The increment of nitric oxide by LPS, an oxidative str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Kaempferol at both concentrations used (10 µM and 30 µM) reduced the secretion of MCP-1 released by macrophages, and at a 30 µM, it significantly decreased the number of copies of MCP-1 mRNA. Hada et al showed that fisetin (3,3 ′ ,4 ′ ,7-tetrahydroxyflavone) suppressed mRNA expression levels of MCP-1, IL-1β, and iNOS and suppressed NO production in LPS-treated macrophages [45]. Liu et al evaluated the effect of naringin (5,7,4 ′ -trihydroxyflavanone-7-O-neohesperidoside), a glycoside of naringenin, on chemokine expression in LPS-induced RAW 264.7 macrophages [46].…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol at both concentrations used (10 µM and 30 µM) reduced the secretion of MCP-1 released by macrophages, and at a 30 µM, it significantly decreased the number of copies of MCP-1 mRNA. Hada et al showed that fisetin (3,3 ′ ,4 ′ ,7-tetrahydroxyflavone) suppressed mRNA expression levels of MCP-1, IL-1β, and iNOS and suppressed NO production in LPS-treated macrophages [45]. Liu et al evaluated the effect of naringin (5,7,4 ′ -trihydroxyflavanone-7-O-neohesperidoside), a glycoside of naringenin, on chemokine expression in LPS-induced RAW 264.7 macrophages [46].…”
Section: Discussionmentioning
confidence: 99%
“…It should also be emphasized that a number of the substances described below have not been registered as medicinal products by the FDA and the European Medicines Agency [ 90 , 91 ]. In TCM, these substances are attributed with anti-inflammatory effects (osthole [ 92 , 93 , 94 , 95 , 96 , 97 ], flavonoids [ 98 , 99 , 100 ]); have been proposed for use in heart disease (salvianolic acid C [ 101 , 102 ]), rheumatoid arthritis (sinomenine [ 103 ]), cardiovascular disease, gastrointestinal and respiratory infections (baicalin [ 104 ]); however, they also have very broad and non-specific indications (liquiritin [ 105 ], praeruptorin A [ 106 ], piperine [ 107 ], rosmarinic acid [ 108 ]).…”
Section: Traditional Chinese Medicines and Plant-derived Compoundsmentioning
confidence: 99%
“…Another natural flavonoid that possesses a range of potential health-related bioactive properties is fisetin ( Figure 2 ). Fisetin is found in various fruits and vegetables [ 140 , 141 ] and has been proposed to have anti-inflammatory [ 99 ] and antiallergic effects ( Table 1 ) [ 100 ]. It has been reported to inhibit several signalling pathways in vitro, including PI3K-Akt-mTOR, P38, and NF-κB [ 142 , 143 ], which were associated with an inhibitory effect in human inflammatory skin models [ 144 ].…”
Section: Traditional Chinese Medicines and Plant-derived Compoundsmentioning
confidence: 99%
“…Fisetin (Fis) is a polyphenolic flavonoid widely found in a variety of vegetables, fruits, and plants of the Lacinia family . To date, Fis has shown unique biological and functional properties, including anti-inflammatory, antioxidant, lipid-lowering, and neuroprotection. , For example, Fis exerted protective effects against cognitive dysfunction induced by lipopolysaccharide (LPS), d -galactose, or Aβ in mice and modulated the gut microbiota to attenuate Parkinson’s disease . Recent studies indicated that Fis treatment effectively augmented the BBB score and fall-off time in SCI rats .…”
Section: Introductionmentioning
confidence: 99%